2020
DOI: 10.1194/jlr.ra119000312
|View full text |Cite
|
Sign up to set email alerts
|

Circulating oxidized LDL, increased in patients with acute myocardial infarction, is accompanied by heavily modified HDL

Abstract: Oxidized LDL (oxLDL) is a known risk factor for atherogenesis. This study aimed to reveal structural features of oxLDL present in human circulation related to atherosclerosis. When LDL was fractionated on an anion-exchange column, in vivo-oxLDL, detected by the anti-oxidized PC (oxPC) mAb, was recovered in flow-through and electronegative LDL [LDL(−)] fractions. The amount of the electronegative in vivo-oxLDL, namely oxLDL in the LDL(−) fraction, present in patients with acute MI was 3-fold higher than that ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 66 publications
1
26
0
Order By: Relevance
“…In vivo oxLDL was modified with oxidized phosphatidylcholine (oxPC) and oxidized HDL [105]. While oxLDL, recognized using the anti-oxPC antibody, was detected in several fractions including LDL(−) fractions, oxLDL in LDL(−) was threefold higher in patients with AMI than in healthy subjects [104]. Our observation is in accordance with previous studies that reported an increase in oxLDL levels in plasma samples from patients with AMI.…”
Section: The Impact Of Modified Ldl and Its Components On Vascular Cellssupporting
confidence: 90%
See 2 more Smart Citations
“…In vivo oxLDL was modified with oxidized phosphatidylcholine (oxPC) and oxidized HDL [105]. While oxLDL, recognized using the anti-oxPC antibody, was detected in several fractions including LDL(−) fractions, oxLDL in LDL(−) was threefold higher in patients with AMI than in healthy subjects [104]. Our observation is in accordance with previous studies that reported an increase in oxLDL levels in plasma samples from patients with AMI.…”
Section: The Impact Of Modified Ldl and Its Components On Vascular Cellssupporting
confidence: 90%
“…Moreover, LDL(−) is enriched with HDL-like particles containing apoA-I heavily modified with acrolein adducts. Electron microscopic analysis revealed that LDL(−) contains heterogeneous and aggregated subpopulations with small-sized particles, similar to HDL [104].…”
Section: The Impact Of Modified Ldl and Its Components On Vascular Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of oxLDL in atheromatous plaques as well as in the circulation has been demonstrated immunologically, where an increase in circulating oxLDL levels was found to be associated with cardiovascular disease [ 4 , 5 , 6 , 7 , 8 ]. In addition, increased circulating oxHDL in patients with cardiovascular diseases and its accumulation in atherosclerotic lesions were also recently demonstrated [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…First of all, a large scale of clinical study must be done to validate the significance of being a novel clinical biomarker. Dr. Sanchez-Quesada and many other study groups published a variety of papers mentioning the clinical prevalence and the pathogenic mechanisms of electronegative LDL [ 103 , 104 , 105 , 106 , 107 , 108 ]. The level difference between patients and controls are comparable, and the atherogenic properties are noticeable.…”
Section: Implication Of L5 Ldlmentioning
confidence: 99%